Use of commercial infant cereals as complementary food in infants and young children in Ghana - Abizari, Abdul-Razak (BMC Nutr, 2017)
BACKGROUND: Typical complementary foods in developing countries are often inadequate in multiple micronutrients. One way of preventing micronutrient deficiency among infants and young children (IYC) is to feed them a variety of nutrient dense foods. The use of commercial infant cereals (CIC) as complementary food is increasing in Ghana. However, it is unknown whether giving CIC may discourage inclusion of other locally available and nutritious foods as mothers may hold the notion that CIC is superior. This study therefore examined the use of CIC as complementary food, the micronutrient intake from CIC and reasons for its use. METHODS: A cross-sectional study was conducted involving mothers with IYC aged 6-23 months who give CIC as complementary food. Questionnaires were administered to estimate the usual daily frequencies and quantities of CIC. Micronutrient intakes from CIC were calculated. We also calculated the proportion of the recommended nutrient intake (RNI) contributed by micronutrients from CIC. RESULTS: Of the 384 children sampled, 64.6% were aged 13-23 months and 50.3% were females. More than half of the mothers earned income through trading (55.2%) and nearly one quarter of them had senior high school education (24.7%). Majority of the children consumed 3–4 tablespoons (52.3%) of CIC in a feeding moment. Younger children (6–12 months) were served CIC more frequent than older children (13–23 months). The mean ± SD of micronutrients from CIC were 6.76 ± 2.67 mg, 4.79 ± 1.70 mg, 384.12 ± 139.69 mg, 266.70 ± 100.74 mg and 69.11 ± 24.65 μg for the minerals Fe, Zn, Ca, P and I respectively. The vitamin intakes were: 337.17 ± 119.70 μg, 42.88 ± 15.28 mg, 0.84 ± 0.31 μg, 34.24 ± 12.22 μg and 2.70 ± 1.03 mg for vitamin A, vitamin C, vitamin B12, folic acid and niacin respectively. Micronutrients from CIC consumption contributed to at least 70% of the RNIs for Fe, Zn, Ca, I, vitamin A, vitamin C and vitamin B12. Mothers believed that CIC alone could meet the nutritional needs of children and ensure optimal growth and health. CONCLUSION: The results of present study show that use of CIC as complementary food was high among mothers with IYC 6–12 months. Mothers believed that CIC was nutritionally adequate for their children and did not see the need to include or enrich other locally available complementary foods. Mothers should be educated on the need to include other foods with CIC to increase the dietary quality of IYC.